Управление эколого-социальными системами на основе интегративной логики и модели предметной области - Прокопчук, Ю.А. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2009)
In work the method of the analysis of management processes in natural subject domains is considered. Tools of a method are integrative logic and model of a subject domain.